2008
DOI: 10.1159/000138121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adlay, Buckwheat and Barley on Lipid Metabolism and Aorta Histopathology in Rats Fed an Obesogenic Diet

Abstract: Background/Aims: The present study was carried out to evaluate the nutritional quality of adlay (AD), buckwheat (BW) and waxy barley (WB), with particular respect to their fiber components. Plasma lipid parameters, gut transit time and thickness of the aortic wall in rats fed with different grains were evaluated and compared with rats fed on white rice (WR). Methods: The rats were then raised for 4 weeks on an obesogenic diet based on the American Institute of Nutrition-93 (AIN-93 G) diets containing 1% choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 61 publications
3
13
0
Order By: Relevance
“…A meta-analyse including 10 studies showed that feeding daily 36 g soy protein with 52 mg soy-associated isoflavones on average decreased LDL-C by -0.17 ± 0.04 mmol/L and increased HDL-C by 0.03 ± 0.01 mmol/L [55]. Buckwheat protein product has a potent hypocholesterolemic activity [56,57]. Son et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analyse including 10 studies showed that feeding daily 36 g soy protein with 52 mg soy-associated isoflavones on average decreased LDL-C by -0.17 ± 0.04 mmol/L and increased HDL-C by 0.03 ± 0.01 mmol/L [55]. Buckwheat protein product has a potent hypocholesterolemic activity [56,57]. Son et al .…”
Section: Discussionmentioning
confidence: 99%
“…Son et al . [57] found that plasma lipid profiles in rats differed significantly according to grain combination. The levels of TG in the adlay, buckwheat and waxy barley groups were significantly lower than those in the white rice group.…”
Section: Discussionmentioning
confidence: 99%
“…Son et al [53] reported that rats consuming barley-based high fat diet had larger aortic lumen and thinner wall thickness than rats consuming a rice-based diet, which is suggestive of a reduction in the accumulation of lipid and/or plaque in the cardiovascular system of these animals. They also showed that plasma triglyceride, total and LDL cholesterol was reduced by the barley diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, animal experiments have revealed that treatment with buckwheat improves hypertension ( 11 , 12 ), obesity (12)(13)(14), and hyperlipidemia (14)(15)(16)(17)(18)(19)(20). In addition, treatment with concentrated buckwheat bran extracts (BBE) reduces plasma glucose in both streptozotocin-induced diabetic rats ( 21 ) and the KK-Ay mouse model for type 2 diabetes ( 22 ).…”
mentioning
confidence: 99%